A comparative exploratory study on framing of Philippine and Chinese state-owned media on the West Philippine Sea dispute - Chua, Christian C.; Lizardo, Rianne Krystiana Q.
Guided by Johan Galtung’s peace and war journalism framework, this study examines the frames employed by Chinese and Philippine state news media about the West Philippine Dispute from 2019 to 2024 and investigates how they are constructed through the use of framing and reasoning devices. Using a combination of content and textual analysis of articles published by leading Philippine and Chinese state media outlets, findings show that both Philippine and Chinese state media predominantly employed war-oriented indicators in their reporting, with a notable increase following President Ferdinand Marcos Jr.’s renewed alignment with the United States. Both governments also relied on strategic reasoning and framing devices to legitimize their maritime claims, justify diplomatic and military actions, and cast the opposing side as the aggressor. Despite the differing narratives, both countries’ coverage lacked grassroots perspectives and critical context needed that could have enriched the public’s understanding of the dispute. Ultimately, the study’s findings highlight the pressing need for state media to shift away from conflict-driven narratives and toward more peace-oriented reporting that serves the broader public interest.